Treatment of morphea - Junjie CEN; Mingjie HE; Guangji GUI; Zhen FENG; Lixian LIN; Lin CHEN; Qing GUO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Morphea is a fibrotic disease that primarily affects the skin and adjacent tissues, with uncertain pathogenesis. At present, there is no etiology-specific treatment available. In recent years, progress has been made in the treatment of morphea, including topical therapy, systemic therapy, UV phototherapy, laser therapy and surgical therapy in China and other countries. This review comprehensively and systematically outlines and summarizes relevant progress, in order to provide references for the research in morphea.